2018
DOI: 10.1021/acs.macromol.8b00297
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Impact Resistance of Polymer Blends via Self-Assembled Nanoscale Interfacial Structures

Abstract: We have designed and engineered an environmentally sustainable ternary polymer blend with the mechanical properties comparable to high impact resistant conventional polymers under the guidance of the lattice self-consistent field model. In this blend system, poly­(methyl methacrylate) (PMMA) was used as the compatibilizer for the poly­(lactic acid) (PLA)/poly­(butylene adipate-co-butylene terephthalate) (PBAT) blend. We characterized the compatibility of those components and found PMMA was miscible with PLA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 49 publications
0
49
0
1
Order By: Relevance
“…Thus, we believed that the 19k‐CL x LA y could partly be dispersed in the PLLA matrix and the PCL phases with increasing the content of 19k‐CL x LA y in the PLA/PCL/19k‐CL x LA y blends. In addition, with the compatibilizer partly dispersed into the matrix polymer as a modifier, its brittleness would decrease the elongation at break of the blends; this phenomena was explained by Guo et al When the content of compatibilizer poly (methyl methacrylate) (PMMA) was higher than 10 wt%, they found that PMMA partly dispersed into the PLLA phase as a modifier and decreased the elongation at break of the PLLA/poly (butylene adipate‐co‐butylene terephthalate) blends. Compared with 19k‐CL 19 LA 81 , the 19k‐CL 51 LA 49 had better flexibility for the composition with 50 wt% CL units and 50 wt% LA units.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, we believed that the 19k‐CL x LA y could partly be dispersed in the PLLA matrix and the PCL phases with increasing the content of 19k‐CL x LA y in the PLA/PCL/19k‐CL x LA y blends. In addition, with the compatibilizer partly dispersed into the matrix polymer as a modifier, its brittleness would decrease the elongation at break of the blends; this phenomena was explained by Guo et al When the content of compatibilizer poly (methyl methacrylate) (PMMA) was higher than 10 wt%, they found that PMMA partly dispersed into the PLLA phase as a modifier and decreased the elongation at break of the PLLA/poly (butylene adipate‐co‐butylene terephthalate) blends. Compared with 19k‐CL 19 LA 81 , the 19k‐CL 51 LA 49 had better flexibility for the composition with 50 wt% CL units and 50 wt% LA units.…”
Section: Resultsmentioning
confidence: 97%
“…Melt blending or compounding PLLA with different types of flexible polymers was one of the economic approaches to toughen PLLA . However, poly(ε‐caprolactone) (PCL) was a biodegradable aliphatic polyester with high flexibility and good biocompatibility and thermal stability, which had gained great attention as modifiers for PLLA, and the modifying results exhibited some improvements in the toughness of PLLA .…”
Section: Introductionmentioning
confidence: 99%
“…7 As mentioned in the beginning, toughening modification with acceptable stiffness and strength is so important in the application, which holds an absolutely large part of the research, especially on brittle polymers such as PLA. 8 Toughening the brittle polymers, incorporating a rubber phase or melt blending with other tough elastomers, 9 optimizing morphologies of the blends such as core–shell structures, 10 and adding a third polymer 11 or filler (microfibers or nanofillers) to the polymer matrix 6 to increase the blend compatibility have been used as main approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, tens of billion tons of plastics are widely used in industrial, agricultural, national defense, healthcare and other fields [1], where most are extracted from petroleum resources. With the increased usage of pertrochemical-based plastics, it causes serious environmental pollution and wastes of oil resources [2,3]. Therefore, the environmentally friendly biobased and biodegradable plastics as well as less persistent and toxic, low carbon green have attracted wide concerns [4,5].…”
Section: Introductionmentioning
confidence: 99%